What the women of Dublin did with John Locke - Gerrard, C (Cambridge University Press, 2020)
William Molyneux's friendship with John Locke helped make Locke's ideas well known in early eighteenth-century Dublin. The Essay Concerning Human Understanding was placed on the curriculum of Trinity College in 1692, soon after its publication. Yet there has been very little discussion of whether Irish women from this period read or knew Locke's work, or engaged more generally in contemporary philosophical debate. This essay focuses on the work of Laetitia Pilkington (1709–1750) and Mary Barber (1685–1755), two of the Dublin women writers of the so-called ‘Triumfeminate’, a literary and intellectual circle connected to Jonathan Swift which met and discussed ideas at the home of Patrick Delaney. Pilkington and Barber were particularly influenced by Locke's ideas on obstetrics and childhood in his Some Thoughts Concerning Education and especially by his discussion of memory in the Essay Concerning Human Understanding. Both authors engage playfully and imaginatively with Locke's theories, especially in a domestic context. Not all philosophical debates took place in the public male spaces of school, coffee house and university. This essay attempts to recreate the contexts in which intellectually curious women of the ‘middling sort’ encountered and engaged with philosophical ideas, especially those of Locke, and how these shaped their writing.